Defect Reduction with the Use of Seven Quality Control Tools for Productivity Improvement at an Automobile Company - Memon, I. A.; Jamali, Q. B.; Jamali, A. S.; Abbasi, M. K.; Jamali, N. A.; Jamali, Z. H. (Engineering, Technology & Applied Science Research, 2019)
The goal of zero defects is pursued by many manufacturing and service companies. In this regard, statistical tools are being used for defect reduction leading to productivity improvement. In this work, seven traditional QC tools (flow chart, check sheet, histogram, Pareto chart, cause, and effect diagram, scatter diagram and control chart) have been developed and implemented in an automobile company to assess and improve the defect reduction level in the assembly line. Chassis and trim lined were selected for data collection to assess and improve the defect level for productivity improvement. It was found from the results that after the successful implementation of the QC tools, the defect level reduced by 90% (from 132 to 13 defects) at the chassis line. Similarly, the defect level was reduced by 80% (from 157 to 28 defects) at the trim line. The automobile company implemented only a few of the seven QC tools in their assembly line. It is suggested that the company may need to manage a mechanism for the implementation of all seven QC tools in every section of the company.